2020
DOI: 10.35838/jrap.2020.007.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Interest Rate Risk in Credit Risk on Bank Performance: Evidence in Indonesia

Abstract: ABSTRACT        This study aims to empirically examine the effect of liquidity on bank performance through the inclusion of interest rate risk on credit risk (INRISK) as a mediator. Where the inclusion of interest rate risk in credit risk (INRISK) is a novel concept developed from the synthesis of monetary theory, financial intermediation theory and liquidity theory, as an attempt to mediate the research gap between the effect of liquidity on bank performance. This study uses panel data with 30 companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 1 publication
2
8
1
1
Order By: Relevance
“…The assumption is that when bad credit occurs, bank management will look for the best solution, one of which is the funds stored in bank capital which can be used in the event of default by customers due to various reasons, one of which is an increased interest rate, in line with ), Safitri, Taolin, et al (2020, Wahyudi et al (2020), include interest rate risk in credit risk and find that the greater credit risk, which is indicated by an increase in customer default, will reduce bank performance.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption is that when bad credit occurs, bank management will look for the best solution, one of which is the funds stored in bank capital which can be used in the event of default by customers due to various reasons, one of which is an increased interest rate, in line with ), Safitri, Taolin, et al (2020, Wahyudi et al (2020), include interest rate risk in credit risk and find that the greater credit risk, which is indicated by an increase in customer default, will reduce bank performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini tidak sejalan dengan penelitian Al Zaidanin dan Al Zaidanin (2021) menyatakan bahwa CAR tidak memiliki pengaruh terhadap kinerja keuangan (ROA). Tetapi penelitian ini didukung oleh penelitian Safitri et al, (2020)…”
Section: Diskusiunclassified
“…Furthermore, trading volume, EPS, and PER partially have a positive and significant effect on stock prices. Safitri et al, (2020) in her research entitled the effect of deposit rates and exchange rates on stock prices in the banking industry found that simultaneously there is a significant influence between deposit rates and exchange rates on stock prices. Partially, deposit rates and exchange rates have a significant effect on stock prices.…”
Section: Social and Culturementioning
confidence: 99%
“…The deposit interest rate variable in the research of Safitri et al, (2020) partially has a significant effect on stock prices. However, this did not occur in research conducted by Wulandari et al, (2009) and research conducted by (Stefanus & Robiyanto, 2020).…”
Section: Social and Culturementioning
confidence: 99%